Synthesis, characterization and antimalarial activity of isoquinoline derivatives - Sewan Theeramunkong (2020)
© 2020, Springer Science+Business Media, LLC, part of Springer Nature. This paper presents synthesis of novel decorated isoquinolines that can be used as antimalarial agents. Two series of compounds, isoquinoline phenyl and isoquinoline triazole derivatives, were synthesized via the Suzuki–Miyaura and Sharpless–Fokin reactions respectively. The final compounds were investigated for their antimalarial activity in cell-based experiments. In the series of isoquinoline phenyl derivatives, compound 6 exhibited interesting antiplasmodial activity against chloroquine resistant (K1) and chloroquine sensitive (3D7) strains of P. Falciparum with IC50 1.91 ± 0.21 μM and 2.31 ± 0.33 μM, respectively. In the series of isoquinoline-triazole derivatives, compound 15 was the most active against resistant (K1) and sensitive (3D7) strains of P. falciparum with IC50 4.55 ± 0.10 μM and 36.91 ± 2.83 μM, respectively. The respective resistance indices of compounds 6 and 15 against K1 and 3D7 were 0.83 and 0.12. Compound 15 was promisingly effective against the resistant strain. The results of this study provided useful contributions for further lead discovery and lead modification of modern rational drug design.